Aristotle's notion of physis and its implications for his thics - Akarsu, Cansu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
This thesis aims to analyze Aristotle's conception of eudaimonia, human well-being, with a view to his understanding of physis, nature. It focuses on the effects of Aristotle's teleological understanding of nature on his ethical doctrine presented in the Nicomachean Ethics. The second chapter elaborates on the relationship between the natural constitution of human beings and the basis of Aristotle's system of ethics. An analysis of the function argument and Aristotle's classification of the rational and non-rational parts of the soul in De Anima is provided to explain Aristotle's conception of the good and its role on his notion of eudaimonia. This analysis particularly aims to clarify the way in which Aristotle conceives the ultimate goal of human beings through their political and physical nature. The last chapter investigates Thomas Nagel's and John Lloyd Ackrill's opposing accounts of eudaimonia focusing on the question of whether Aristotle's notion of eudaimonia is suggestive of a life of theoretical contemplation as it is defended by Nagel's intellectualist account, or it comprehends the excellence of the different activities of human beings which have a composite nature. In the final analysis, the latter account which is discussed through Ackrill' s inclusive account is defended to explain Aristotle's notion of eudaimonia which stands for the ultimate goal of human beings in agreement with the political and physical nature that are essentially belonging and determinative over their ultimate good.
Keywords: Philosophy, Ancient.